2015
DOI: 10.4028/www.scientific.net/kem.670.232
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Materials on the Basis of Yttrium Oxide and Yttrium Aluminum Garnet Used for Photodynamic Therapy

Abstract: Finely-dispersed phosphors of Y2O3:Eu and Y3Al5O12:Eu have been synthesized with the help of Pechini method and the method of self-propagating high-temperature synthesis (SHS). During the synthesis of phosphors on the basis of Y2O3 carried out with Pechini method the size of crystallites increases with the enlargement of concentration of yttrium, but it decreases when the method of SHS is applied. The structure of phosphors on the basis of Y3Al5O12 (YAG) is strongly amorphized. This fact agrees with the data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
4
8
0
Order By: Relevance
“…Using Sharer formula crystallite sizes were calculated, Table II, it can be seen that increase in dopant concentration leads to change in crystallite size that has different tendency depending on synthetic rout, similar behavior for Y2O3:Eu 3+ phosphor was observed in our previous work [4] and also described above for NaBaPO4. Europium ions may substitute Zn 2+ or Al 3+ sites in spinel matrix or locate on surfaces of nanoparticles due to their porosity.…”
Section: Znal2o4:eu 3+ Phosphorssupporting
confidence: 76%
See 1 more Smart Citation
“…Using Sharer formula crystallite sizes were calculated, Table II, it can be seen that increase in dopant concentration leads to change in crystallite size that has different tendency depending on synthetic rout, similar behavior for Y2O3:Eu 3+ phosphor was observed in our previous work [4] and also described above for NaBaPO4. Europium ions may substitute Zn 2+ or Al 3+ sites in spinel matrix or locate on surfaces of nanoparticles due to their porosity.…”
Section: Znal2o4:eu 3+ Phosphorssupporting
confidence: 76%
“…Phosphor's luminescent properties determines their quality and applications. Luminescence depend on a number of factors, such as chemical composition, crystal structure, dopants, etc., and can be controlled using various synthetic technique and treatments [1][2][3][4]. It is well known, that for the efficient luminescence, especially cathodoluminescence, crystallite size is very important, since boundaries between crystallites play role of non-radiative recombination sites [3].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, much attention was paid to the investigation of the phosphors surface properties without a detailed consideration of the effect of the matrix structure on the corresponding luminescent transitions. In the previous studies [19][20][21], we have shown that acid-base active sites, dispersity, and porosity reflect the imperfection of the solids surface structure and affect the luminescent properties of materials sensitive to the surface state. This study shows that the phosphors based on YVO 4 had more intense PL and increased brightness compared with the samples based on YPO 4 .…”
Section: Excitation and Luminescencementioning
confidence: 98%
“…In summary, the synthesis of mixed yttrium vanadate-phosphate phosphors provides an increase in PL brightness compared with both individual components due to their interphase interactions yielding new surface compounds. This approach is promising for the further optimization of the compositions of the phosphors to improve their performance [20][21][22].…”
Section: Excitation and Luminescencementioning
confidence: 99%
“…Phosphor's luminescent properties determines their quality and applications. Luminescence depend on a number of factors, such as chemical composition, crystal structure, dopants, etc., and can be controlled using various synthetic technique and treatments [1][2][3][4]. It is well known, that for the efficient luminescence, especially cathodoluminescence, crystallite size is very important, since boundaries between crystallites play role of non-radiative recombination sites [3].…”
Section: Introductionmentioning
confidence: 99%